Management of Hybrid Corn Technology Application in Gorontalo - Husin Tabrani; Kaimuddin; Syatrianty Andi Saiful (Journal of Public Administration and Government, 2023)
The study's purpose was to assess hybrid maize varieties' tolerance to shade as well as their reaction to fertilization. From August 2021 to November 2021, the research was conducted in Molowahu village, Tibawa sub-district, Gorontalo regency, Gorontalo province. The first element in this study was hybrid maize varieties consisting of three levels, namely Nasa-29, JH-29, and Bisi-18, and the second factor was environmental design (RAK). The usage of fertilizers, namely NPK Phonska 300 kg/ha + Urea 200 kg/ha, manure 1 ton/ha + NPK Phonska 150 kg/ha + Urea 100 kg/ha, and manure 2 tons/ha, is the second factor. The findings of this study revealed that the Nasa-29 variety had the best amount of shade tolerance, as evidenced by the maximum yield of 6.77 tons/ha. A fertilizer package of 1 ton/ha manure + Phonska NPK 150 kg/ha + Urea 100 kg/ha can boost and optimize the development and output of maize plants in the shade between coconut plants by 0.44 tons/ha, with no interaction between variety treatment and the fertilization package.